The hero code lessons learned from lives well lived - Admiral William H. McRaven (New York, NY Hachette Audio, 2021)
THE HERO CODE is Admiral McRaven's ringing tribute to the real, everyday heroes he's met over the years, from battlefields to hospitals to college campuses, who are doing their part to save the world.
Keywords: McRaven, William H. (William Harry), 1955---Anecdotes.